easyPACId, a Simple Method for Induced Production, Isolation, Identification, and Testing of Natural Products from Proteobacteria - Edna Bode; Daniela Assmann; Petra Happel; Elmar Meyer; Karin Münch; Nicole Rössel; Helge Bode (Bio-Protocol, 2023)
The easyPACId (easy Promoter Activation and Compound Identification) approach is focused on the targeted activation of natural product biosynthetic gene clusters (BGCs) encoding non-ribosomal peptide synthetases (NRPS), polyketide synthases (PKS), NRPS-PKS hybrids, or other BGC classes. It was applied to entomopathogenic bacteria of the genera Xenorhabdus and Photorhabdus by exchanging the natural promoter of desired BGCs against the L-arabinose inducible PBAD promoter in ∆hfq mutants of the respective strains. The crude (culture) extracts of the cultivated easyPACId mutants are enriched with the single compound or compound class and can be tested directly against various target organisms without further purification of the produced natural products. Furthermore, isolation and identification of compounds from these mutants is simplified due to the reduced background in the ∆hfq strains. The approach avoids problems often encountered in heterologous expression hosts, chemical synthesis, or tedious extraction of desired compounds from wild-type crude extracts. This protocol describes easyPACId for Xenorhabdus and Photorhabdus, but it was also successfully adapted to Pseudomonas entomophila and might be suitable for other proteobacteria that carry hfq.